Screening of Hybrid Jatropha curcas L. Genotypes for Drought Tolerant Abilities as a Source of Superior Variety Characteristics - Erfan Dani Septia; Siti Rofidah; Sofyan Arief; Maftuchah Maftuchah (Universitas Sebelas Maret, 2021)
The scarcity of fuel oil in the future needs to be anticipated by preparing alternative energy. One of the alternative energy sources developed is Jatropha. However, the development of Jatropha should use marginal land as a cultivation area, like a dry land, because the food crops and horticulture use productive land for cultivation. Furthermore, Jatropha development through breeding is an effort to obtain superior varieties as biodiesel producers. This study aimed to determine the best phenotype characteristics of hybrid Jatropha plants as superior candidate trees. This research applied a descriptive qualitative method to determine the characteristics of Jatropha crossing results. The Jatropha characterization was conducted at the experimental garden of Kedung Pengaron Village, Kejayan Sub-district, Pasuruan Regency. The experimental garden was included dry land for Jatropha cultivation. The result showed ten selected genotypes of hybrid Jatropha were found, including 05.01.01, 05.01.02, 05.02.02, 05.02.09, 05.03.17, 05.03.16, 05.04.16, 05.04.15, 06.01.02, 06.01.15. These were based on the two-phase observations, consisting of vegetative and generative observations. The plants’ morphological characters were observed, comprising the stems, leaves, flowers, fruits and seeds. In the vegetative phase, diversity was found in the number of leaves, leaf length and age of flowering, while in the qualitative phase, the shoot colors were more diverse. Moreover, less variations were figured out in the color character of the petiole and the number of shoots. These ten genotypes of hybrid Jatropha are the best genotypes that are resistant to drought with selected agronomic characters.